(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the effect of Dapagliflozin on BMI and HbA1C in Type 2 Diabetic Patients Study Design: Retrospective / observational study. Place and Duration of Study: This study was conducted at the internal department of Medicine, Khyber Teaching Hospital Peshawar from August 2020 to July 2021. Materials and Methods: Total 333 diabetic patients, with mean age of 45.66 years, were enrolled in the study. Average BMI was 32.8 while average HbA1C was 9.94% at the time of enrollment. After taking prior informed consent and documentation of the demographic profile of the patients, SGLT2 inhibitors (Dapa) 10 mg was given for the treatment of T2DM. The main aim was reduction in HbA1C and BMI. Both BMI and HbA1C level was recorded at 0 months and 6 months. The statistical analysis was done using SPSS version 22.0 and graph were constructed using GraphPad prism software Results: In total 333 diabetic patients, 39.9% (133) were females and 60.1% (200) were males. The mean age was 45.66 ± 8.3 years. The mean HbA1c at initial enrollment was 9.94 ± 0.53% and at follow-up, it was 8.42 ± 0.74%. Similarly, the mean BMI was 23.8 ± 1.1 at the time of enrollment, which was reduced to 31.4 ± 1.2 after follow-up. Statistically significant difference was recorded between initial and follow-up HbA1c values with p-value and 95%CI <0.001, -1.5-1.5. Similarly, the mean BMI reduction was significant from 32.8 ± 1.1 to 31.4 ± 1.2 with a p-value, 95%CI <0.001, -1.4-1.2. Conclusion: SGLT-2 inhibitor, dapagliflozin is a very good anti-diabetic drug with additional benefits of BMI reduction.